Liquid crystal polyester-based resin composition, liquid crystal polyester-based film using the composition, and metal laminate film and circuit board which use the film

The liquid crystal polyester resin composition, combining thermoplastic liquid crystal polyester with a non-crystalline copolyester, addresses the issues of high-frequency electrical instability and dimensional changes in conventional films by stabilizing film formation and improving mechanical and electrical properties, making it suitable for high-speed communication applications.

JP2025013240APending Publication Date: 2025-01-24OKURA INDUSTRIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024108952
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2024-07-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional insulating films made from materials like polyimide and polyethylene terephthalate suffer from inadequate electrical characteristics in high-frequency regions due to high moisture absorption, leading to dimensional changes and difficulty in achieving films that meet the demands for miniaturization and mechanical stability in electronic equipment.

Method used

A liquid crystal polyester resin composition is developed by blending thermoplastic liquid crystal polyester with a non-crystalline copolyester having a glass transition temperature of 80 to 200°C, which stabilizes film formation during inflation molding by reducing viscosity dependence on temperature and improving sliding properties near the softening point, thereby suppressing wrinkles and slack.

Benefits of technology

The composition enables the production of smooth, stable films with excellent mechanical, electrical, and heat-resistant properties, suitable for high-speed communication applications, by maintaining film integrity and reducing friction during extrusion molding processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013240000001
    Figure 2025013240000001
  • Figure 2025013240000002
    Figure 2025013240000002
Patent Text Reader

Abstract

To provide a liquid crystal polyester resin composition which suppresses slacks and wrinkles of a film in extrusion molding such as an inflation extrusion molding method, enables stable formation of a film, and is excellent in mechanical characteristics, electric characteristics and heat resistance.SOLUTION: A liquid crystal polyester-based resin composition contains thermoplastic liquid crystal polyester (A) and amorphous copolyester (B), wherein the amorphous copolyester (B) has a glass transition temperature of 90°C or higher and 200°C or lower, and a blending ratio (A):(B) of the thermoplastic liquid crystal polyester (A) and the amorphous copolyester is 50 to 99 wt.%:1 to 50 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal polyester resin composition containing a thermoplastic liquid crystal polyester capable of forming an optically anisotropic molten phase as a main component, a liquid crystal polyester film using the resin composition, and a metal laminate film and a circuit board using the film. [Background technology]

[0002] In recent years, there has been a growing demand in the electronics and electrical fields for smaller and lighter devices, and insulating films with excellent electrical and mechanical properties are in demand. However, conventional raw materials for insulating films, such as polyimide and polyethylene terephthalate, have insufficient electrical properties in the high frequency range, and are highly hygroscopic, which can lead to poor electrical properties and large dimensional changes, making it difficult to create films that meet the above requirements.

[0003] Thermoplastic liquid crystal polyester has been attracting attention as a material for flexible printed circuit (FPC) boards and other devices due to its excellent mechanical properties such as heat resistance and rigidity, chemical resistance, and dimensional accuracy, as well as its excellent electrical properties (low dielectric constant, low dielectric tangent) in the high frequency range (GHz band) and low transmission loss in circuits.

[0004] Thermoplastic liquid crystal polyester can be formed into a film by various extrusion molding methods. However, a film formed by a T-die extrusion molding method shows anisotropy in the molecular chain orientation in the take-up direction (MD direction) and the direction perpendicular thereto (TD direction) because the thermoplastic liquid crystal polyester has a rigid molecular structure and the molecules tend to be oriented in the flow direction in a molten state, making it difficult to obtain a thermoplastic liquid crystal polyester film with isotropic molecular chain orientation.

[0005] In contrast, the inflation extrusion molding method makes it possible to stretch the molten thermoplastic liquid crystal polyester extruded from an annular die in both MD and TD directions, and therefore makes it easy to obtain an isotropic thermoplastic liquid crystal polyester film by appropriately adjusting the blow ratio and controlling the orientation of the molecular chains.

[0006] However, the melt viscosity of thermoplastic liquid crystal polyester is highly dependent on shear stress and temperature, and a slight increase in shear stress or temperature causes a significant decrease in melt viscosity. Therefore, when the thermoplastic liquid crystal polyester is melt-extruded by the inflation extrusion molding method, the shear stress and temperature increase generated in the die portion can cause a sudden decrease in melt viscosity, making it difficult to maintain the bubble shape, resulting in a problem that it is difficult to stably produce a film.

[0007] Patent Document 1 is an invention relating to a polymer alloy consisting of a thermoplastic polymer (thermoplastic liquid crystal polymer) capable of forming an optically anisotropic molten phase and an amorphous polymer, and describes that by blending a polyarylate resin with a thermoplastic liquid crystal polymer, the film-forming stability in the inflation method can be improved; more specifically, it describes that the lateral shaking of the bubble extruded from the annular die is prevented, the amount of displacement is reduced, and stable film formation is maintained.

[0008] Patent Document 2 is an invention relating to a liquid crystal polymer composition containing a liquid crystal polymer and a polyarylate resin, and describes that blending a polyarylate resin with a liquid crystal polymer improves melt tension and provides excellent film-forming properties in extrusion molding. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent Publication No. 2000-290512 [Patent Document 2] Patent Publication No. 2020-193261 Summary of the Invention [Problem to be solved by the invention]

[0010] However, thermoplastic liquid crystal polyesters have a high tensile modulus and a small elongation at break, and therefore have high rigidity. When produced into a film by inflation extrusion molding, the film tends to wrinkle and sag, making it difficult to obtain a smooth film.

[0011] For example, in the inflation extrusion method, molten resin is extruded from an annular slit into a bubble shape, and air or inert gas is blown into the inside of the bubble made of the molten resin to expand and stretch the bubble in the MD and TD directions. The expanded and stretched bubble is gradually folded flat while being brought into contact with a pair of stabilizers that are inclined so that the downstream sides in the MD direction are close to each other, and is guided to pinch rolls, where the bubble is folded flat by the pair of pinch rolls. However, in the process of folding a cylindrical bubble flat while being brought into contact with the stabilizer plates and folding it flat by the pinch rolls, the bubble located at the center of the stabilizer plates and the bubbles located at both ends of the stabilizer plates have geometrically different linear distances from the position where the bubble directly contacts the stabilizer plates to the pinch rolls. Therefore, if the resin is highly rigid, the film cannot deform when it is nipped flat between the pinch rolls, and sagging and wrinkles in the MD direction (vertical wrinkles) occur in the film.

[0012] For this reason, when forming a film from a thermoplastic liquid crystal polyester by inflation extrusion molding, it is effective to control the resin temperature of the bubble when folding the bubble into a flat shape between pinch rolls to near the softening point so that the film is easily deformed, and to suppress the occurrence of slackness and vertical wrinkles in the film. On the other hand, if the resin temperature of the bubble is controlled to near the softening point up to the pinch roll position, the sliding property of the bubble near the softening point is insufficient, and crescent-shaped wrinkles (horizontal wrinkles) occur in the bubble in the TD direction due to friction between the bubble and the stabilizer, which creates a new problem that it is difficult to obtain a smooth film.

[0013] The present invention has been made in consideration of such problems, and an object of the present invention is to provide a liquid crystal polyester resin composition which suppresses the occurrence of slackness and wrinkles in a film during extrusion molding such as inflation extrusion molding, and which has excellent mechanical properties, electrical properties, and heat resistance and enables stable film formation. [Means for solving the problem]

[0014] The present inventors have conducted extensive research into a resin composition that maintains the mechanical properties, electrical properties, heat resistance, etc. of thermoplastic liquid crystal polyester while suppressing the occurrence of slackness and wrinkles in the film and enables stable film formation. As a result, they have found that by blending an amorphous copolyester having a glass transition temperature of 80 to 200°C into a thermoplastic liquid crystal polyester, it is possible to suppress the occurrence of slackness and wrinkles in the film during extrusion molding such as inflation extrusion film formation, and to achieve stable film formation, thereby completing the present invention.

[0015] According to the present invention, (1) A liquid crystal polyester-based resin composition comprising a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B), wherein the amorphous copolyester (B) has a glass transition temperature of 80°C or higher and 200°C or lower, and the blending ratio of the thermoplastic liquid crystal polyester (A) to the amorphous copolyester is (A):(B)=50-99.5% by weight:0.5-50% by weight, (2) The liquid crystal polyester resin composition according to (1) is provided, characterized in that the thermoplastic liquid crystal polyester (A) contains at least one selected from the group consisting of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid; (3) The liquid crystal polyester resin composition according to (1), wherein the amorphous copolyester (B) contains a structural unit derived from a terephthalic acid monomer and a structural unit derived from 1,4-cyclohexanedimethanol, (4) The liquid crystal polyester resin composition according to (1) is provided, characterized in that the amorphous copolyester (B) contains a structural unit derived from a terephthalic acid monomer, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol; (5) The liquid crystal polyester resin composition according to (1) is provided, characterized in that the thermoplastic liquid crystal polyester (A) has a melting point of 250° C. or higher; (6) The liquid crystal polyester resin composition according to (1) is provided, which is for use in inflation extrusion molding; (7) A liquid crystal polyester film comprising the resin composition according to any one of (1) to (6), (8) A metal laminate film is provided, characterized in that a metal layer is laminated on one or both sides of the liquid crystal polyester film according to (7), (9) There is provided a circuit board comprising at least one conductor layer and the liquid crystal polyester film according to (7). Effect of the Invention

[0016] The liquid crystal polyester resin composition of the present invention contains an amorphous copolyester having a glass transition temperature of 80 to 200 ° C., and thus the dependency of the melt viscosity of the resin composition on temperature and shear stress can be reduced. Therefore, when a film is produced by extrusion molding such as inflation extrusion molding, the lateral vibration of the bubble extruded from the die can be suppressed, and the occurrence of holes in the bubble can be suppressed, and a film can be stably produced. In addition, since the sliding property near the softening point of the resin composition can be improved, the occurrence of wrinkles due to friction with the stabilizer can be suppressed in extrusion molding such as inflation extrusion molding, and a smooth film without slack or wrinkles can be obtained. Furthermore, it is possible to maintain the excellent mechanical properties, electrical properties, and heat resistance of the thermoplastic liquid crystal polyester while improving the film production processability. Therefore, the liquid crystal polyester film made of the liquid crystal polyester resin composition of the present invention and the metal laminate film obtained by laminating the liquid crystal polyester film and a metal layer have excellent mechanical properties, electrical properties, and solder reflow properties, and can be suitably used for applications such as laminates for circuit boards suitable for high-speed communication applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and various embodiments can be made within the scope of the effects of the present invention.

[0018] [Liquid crystal polyester resin composition] The liquid crystal polyester resin composition of the present invention is a resin composition containing a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B). By blending the amorphous copolyester (B) having a glass transition temperature of 80°C or more and 200°C or less, a smooth film can be stably produced in extrusion molding such as inflation film production. Although the reason for this is unclear, it is presumed that the melt viscosity of the resin composition is less dependent on temperature and shear stress, so that the lateral vibration of bubbles extruded from a die and the formation of holes in the bubbles can be suppressed in extrusion molding such as inflation extrusion molding, and a film can be stably produced. In addition, by blending the amorphous copolyester (B) having a glass transition temperature of 80°C or more and 200°C or less, the sliding property near the softening point of the resin composition is improved, so that the friction with the stabilizer can be reduced in extrusion molding such as inflation extrusion molding, and a smooth film without slack or wrinkles can be obtained.

[0019] [Thermoplastic liquid crystal polyester (A)] The thermoplastic liquid crystal polyester (A) used in the present invention is a liquid crystal polyester exhibiting melt anisotropy (a polyester capable of forming an optically anisotropic molten phase). The melt anisotropy can be confirmed by a conventional polarized light inspection method using crossed polarizers. Specifically, the melt anisotropy can be confirmed by using a polarizing microscope (manufactured by Olympus Corporation, etc.) to melt a sample placed on a hot stage (manufactured by Linkam Co., Ltd., etc.) and observing the sample at a magnification of 150 times under a nitrogen atmosphere. A liquid crystal resin that exhibits optical anisotropy when melted is optically anisotropic and transmits light when inserted between crossed polarizers. If the sample is optically anisotropic, polarized light will transmit even when the sample is in a molten, stationary liquid state, for example.

[0020] The thermoplastic liquid crystal polyester (A) is not particularly limited in terms of its chemical composition as long as it is a liquid crystal polyester that can be melt-molded, and examples thereof include thermoplastic liquid crystal polyesters having a repeating unit derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids, aromatic or aliphatic diols, aromatic or aliphatic dicarboxylic acids, aromatic diamines, aromatic hydroxyamines, and aromatic aminocarboxylic acids.

[0021] Examples of aromatic hydroxycarboxylic acids include p-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and 4-(4-hydroxyphenyl)benzoic acid. These compounds may have a substituent such as a halogen atom, a lower alkyl group, and a phenyl group. Among them, p-hydroxybenzoic acid or 6-hydroxy-2-naphthoic acid is preferred. Examples of aromatic or aliphatic diols include aromatic diols. Examples of aromatic diols include hydroquinone, 4,4'-dihydroxybiphenyl, 3,3'-dimethyl-1,1'-biphenyl-4,4'-diol, and acylated products thereof, with hydroquinone or 4,4'-dihydroxybiphenyl being preferred. Examples of aromatic or aliphatic dicarboxylic acids include aromatic dicarboxylic acids. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid, with terephthalic acid being preferred. Examples of aromatic diamines, aromatic hydroxyamines, and aromatic aminocarboxylic acids include p-phenylenediamine, 4-aminophenol, and 4-aminobenzoic acid.

[0022] The thermoplastic liquid crystal polyester (A) preferably has at least one repeating unit selected from the group consisting of repeating units represented by the following formulas (1) to (3). -O-Ar1-CO-(1) -CO-Ar2-CO-(2) -X-Ar3-Y-(3) In formula (1), Ar1 represents a phenylene group, a naphthylene group, or a biphenylene group. In formula (2), Ar2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group represented by the following formula (4). In formula (3), Ar3 represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group. -Ar4-Z-Ar5-(4) In formula (4), Ar4 and Ar5 each independently represent a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group. The phenylene group, the naphthylene group and the biphenylene group may have a substituent selected from the group consisting of a halogen atom, an alkyl group and an aryl group.

[0023] In particular, the thermoplastic liquid crystal polyester (A) preferably has at least one repeating unit selected from the group consisting of a repeating unit derived from an aromatic hydroxycarboxylic acid represented by the above formula (1), a repeating unit derived from an aromatic diol represented by the above formula (3) in which X and Y are both oxygen atoms, and a repeating unit derived from an aromatic dicarboxylic acid represented by the above formula (2).

[0024] The thermoplastic liquid crystal polyester (A) preferably has a structural unit derived from an aromatic hydroxycarboxylic acid, more preferably has at least one selected from the group consisting of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid, and even more preferably has a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid.

[0025] In another preferred embodiment, the thermoplastic liquid crystal polyester (A) preferably has at least one selected from the group consisting of a structural unit derived from 6-hydroxy-2-naphthoic acid, a structural unit derived from an aromatic diol, a structural unit derived from terephthalic acid, and a structural unit derived from 2,6-naphthalenedicarboxylic acid, and more preferably has all of a structural unit derived from 6-hydroxy-2-naphthoic acid, a structural unit derived from an aromatic diol, a structural unit derived from terephthalic acid, and a structural unit derived from 2,6-naphthalenedicarboxylic acid.

[0026] The synthesis method of the thermoplastic liquid crystal polyester (A) is not particularly limited, and the above compound can be synthesized by polymerizing it by a known method such as melt polymerization, solid phase polymerization, solution polymerization, and slurry polymerization. As the thermoplastic liquid crystal polyester (A), a commercially available product may be used. Examples of commercially available thermoplastic liquid crystal polyesters include "LAPEROS" manufactured by Polyplastics, "VECTRA" manufactured by Celanese, "UENO LCP" manufactured by Ueno Pharmaceutical, "SUMIKA SUPER LCP" manufactured by Sumitomo Chemical, "ZYDAR" manufactured by ENEOS, and "SIVELAS" manufactured by Toray. The thermoplastic liquid crystal polyester (A) may form a chemical bond with an optional component such as a crosslinking agent or a compatible component (reactive compatibilizer).

[0027] The melting point of the thermoplastic liquid crystal polyester (A) is preferably 250°C or higher. If the melting point is lower than 250°C, the solder reflow property is poor, so that the processing method is limited when used for applications such as printed circuit boards. The melting point of the thermoplastic liquid crystal polyester (A) is not particularly limited, but from the viewpoint of heat resistance and moldability, it is preferably 400°C or lower, more preferably 350°C or lower, even more preferably 330°C or lower, and particularly preferably 300°C or lower. The lower limit of the melting point is more preferably 260°C or higher, and even more preferably 270°C or higher. The melting point of the thermoplastic liquid crystal polyester (A) is determined by using a differential scanning calorimeter (DSC) to completely melt a sample at a rate of 10°C / min, then cooling the molten product to 30°C at a rate of 10°C / min, and then heating it again at a rate of 10°C / min. The melting point is determined by the position of the endothermic peak that appears when the sample is heated at a rate of 10°C / min to melt it completely, and then cooled at a rate of 10°C / min to 30°C.

[0028] [Amorphous copolyester (B)] The amorphous copolyester (B) used in the present invention is a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol, and does not have a clear endothermic peak in thermal analysis using differential scanning calorimetry (DSC). For example, in thermal analysis using DSC, it has only a stepwise endothermic change, is a solid at room temperature, and is thermoplastic at a temperature equal to or higher than the glass transition temperature.

[0029] The amorphous copolyester (B) preferably contains a structural unit derived from a terephthalic acid monomer and a structural unit derived from 1,4-cyclohexanedimethanol. The terephthalic acid monomer is terephthalic acid or a derivative of terephthalic acid. Examples of the derivative of terephthalic acid include halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides, and mixtures thereof of terephthalic acid. Examples of the derivative of terephthalic acid include dialkyl esters and diaryl esters of terephthalic acid, and specific examples thereof include dimethyl terephthalate (DMT) and diethyl terephthalate.

[0030] The amorphous copolyester (B) may further contain a constituent unit derived from another monomer. In one embodiment, it further contains a constituent unit derived from a dicarboxylic acid (other dicarboxylic acid) other than a terephthalic acid monomer. Examples of the other dicarboxylic acid include cyclohexanedicarboxylic acid, isophthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, and stilbene dicarboxylic acid. Examples of the cyclohexanedicarboxylic acid include 1,3- and / or 1,4-cyclohexanedicarboxylic acid. When the amorphous copolyester (B) contains a constituent unit derived from another dicarboxylic acid, the content of the constituent unit derived from a terephthalic acid monomer is preferably 40 mol% or more, more preferably 40 mol% to 90 mol%, and even more preferably 50 mol% to 85 mol% based on the total amount of dicarboxylic acid (the total amount of the constituent units derived from a terephthalic acid monomer and the constituent units derived from the other dicarboxylic acid).

[0031] The amorphous copolyester (B) may further contain a constituent unit derived from a diol (other diol) other than 1,4-cyclohexanedimethanol. Examples of the other diol include aliphatic or alicyclic glycols (preferably having 2 to 20 carbon atoms). Examples of the other diol include ethylene glycol, diethylene glycol, triethylene glycol, propanediol, butanediol, pentanediol, hexanediol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and the like. In one embodiment, the amorphous copolyester (B) further contains a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol. When the amorphous copolyester (B) contains a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), the content of the structural unit derived from 1,4-cyclohexanedimethanol (CHDM) is preferably 10 mol% to 90 mol%, more preferably 20 mol% to 85 mol%, and even more preferably 30 mol% to 80 mol%, based on the total of the structural units derived from TMCD and the structural units derived from CHDM. The content of the structural units derived from TMCD is preferably 10 mol% to 90 mol%, more preferably 15 mol% to 80 mol%, and even more preferably 20 mol% to 70 mol%, based on the total of the structural units derived from TMCD and the structural units derived from CHDM.

[0032] The glass transition temperature (Tg) of the amorphous copolyester (B) is 80°C or more and 200°C or less, preferably 85°C or more and 180°C or less, more preferably 90°C or more and 160°C or less, even more preferably 95°C or more and 150°C or less, and particularly preferably 100°C or more and 140°C or less. The glass transition temperature can be measured by a conventionally known method, for example, by differential scanning calorimetry in accordance with JIS K-7121:2012. In addition, when the manufacturer has a published value for the glass transition temperature, the published value of the manufacturer may be used.

[0033] The liquid crystal polyester resin composition of the present invention contains the above-mentioned thermoplastic liquid crystal polyester (A) and the amorphous copolyester (B) in a ratio of (A):(B)=50-99.5% by weight:0.5-50% by weight. Preferably, (A):(B)=70-99% by weight:1-30% by weight, more preferably, (A):(B)=80-98.5% by weight:1.5-20% by weight, even more preferably, (A):(B)=85-98% by weight:2-15% by weight, and particularly preferably, (A):(B)=90-97.5% by weight:2.5-10% by weight. If the amount of the amorphous copolyester (B) is less than the above range, the effect of reducing the dependency of the melt viscosity of the liquid crystal polyester resin composition on temperature and shear stress is poor, and the effect of improving the sliding property near the softening point of the resin composition is poor, so it is difficult to obtain a smooth film by film formation processing by the inflation extrusion molding method. If the blend amount of the amorphous copolyester (B) is more than the above range, the heat resistance and mechanical properties of the liquid crystal polyester film made of the liquid crystal polyester resin composition may be deteriorated.

[0034] The liquid crystal polyester resin composition of the present invention may contain other resin components other than the above-mentioned thermoplastic liquid crystal polyester (A) and amorphous copolyester (B) within a range that does not impair the effects of the present invention. Examples of other resin components include thermoplastic resins such as polyarylate, polyphenylene sulfide, polyphenylene ether, polyether ether ketone, polyetherimide, cycloolefin polymer, polyamide, polyamideimide, polyimide, epoxy group-containing olefin copolymer, styrene resin, and copolyester elastomer. The liquid crystal polyester resin composition of the present invention may also contain additives such as a compatibilizer, a lubricant, an antioxidant, and a filler. In addition, when the liquid crystal polyester resin composition of the present invention contains other components, it is preferable to contain the total amount of the thermoplastic liquid crystal polyester (A) and the amorphous copolyester (B) as the main component. Here, the main component means that the composition ratio of the components constituting the resin composition is 50% by weight or more, preferably 60% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0035] [Method of manufacturing liquid crystal polyester film] The present invention also proposes a film made of the above-mentioned resin composition and a method for producing the film. The liquid crystal polyester film of the present invention is obtained by blending the above-mentioned thermoplastic liquid crystal polyester (A) and the amorphous copolyester (B) by a known method and forming the blend into a film. When the blending ratio of the amorphous copolyester (B) is reduced, the resin composition of the present invention is preferably melt-kneaded and granulated prior to film formation in order to provide a stable kneaded state.

[0036] The equipment for melt kneading is not particularly limited, and examples thereof include various known extruders such as a batch kneader, a kneader, a co-kneader, a Banbury mixer, a roll mill, a single-screw or twin-screw extruder, etc. Among these, a single-screw extruder or a twin-screw extruder is preferably used because of its excellent kneading ability and productivity.

[0037] The resin composition of the present invention can suppress a sudden drop or change in melt viscosity of the resin composition due to temperature, shear stress, etc., by blending the amorphous copolyester (B), and can improve the film forming processability by inflation extrusion molding. In addition, blending the amorphous copolyester (B) improves the sliding property near the softening point of the resin composition, and can suppress the occurrence of wrinkles due to friction with a stabilizer plate in extrusion molding such as inflation extrusion molding, thereby making it possible to obtain a smooth film without slack or wrinkles.

[0038] An example of the inflation extrusion molding is a method in which the above-mentioned resin composition is fed to a melt extruder equipped with a die having an annular slit, the molten resin composition is extruded upward or downward in a bubble shape from the annular slit of the extruder, and air or an inert gas is blown into the bubble of the molten resin composition from inside to expand and stretch the bubble in a direction (TD) perpendicular to the flow direction (MD) to obtain a film. The cylinder temperature of the melt extruder is usually 260 to 400°C, preferably 280 to 380°C. The interval of the annular slit is usually 0.1 to 5 mm, preferably 0.2 to 2 mm. The diameter of the annular slit is usually 20 to 1000 mm, preferably 25 to 600 mm.

[0039] In inflation extrusion molding, the blow ratio is preferably 1.5 or more, more preferably 2.0 or more, even more preferably 4.0 or more, and particularly preferably 4.5 or more. The upper limit of the blow ratio is not particularly limited, but for example, the blow ratio is 10 or less. The draft ratio is preferably 1.5 to 20, more preferably 1.5 to 10. Here, the blow ratio is the stretch ratio in the TD direction, and the draft ratio is the stretch ratio in the MD direction. When the blow ratio and the draft ratio are in the above range, the anisotropy of the tensile modulus and tensile strength of the obtained film (the difference between the MD direction and the TD direction) can be improved. However, in inflation extrusion molding of a liquid crystal polyester resin composition, increasing the blow ratio to improve the anisotropy of the film works in the direction of destabilizing the shape retention of the bubble made of the resin composition in a molten state, so that the bubble is likely to vibrate or have holes. In contrast, the resin composition of the present invention, by blending the amorphous copolyester (B), can suppress a sudden decrease or change in the melt viscosity of the resin composition due to temperature, shear stress, etc., and therefore can suppress the occurrence of holes in the bubbles even when the blow ratio is 4.0 or more, and can stably produce a film while improving the anisotropy of the film.

[0040] The thickness of the liquid crystal polyester film of the present invention is not particularly limited, but is, for example, 0.5 μm or more and 1000 μm or less. Taking into consideration the handling property and productivity during melt extrusion, the thickness is preferably 5 μm or more and 500 μm or less, more preferably 10 μm or more and 300 μm or less, and even more preferably 20 μm or more and 200 μm or less.

[0041] The liquid crystal polyester film of the present invention preferably has a tensile strength of 180 MPa or more in the machine direction (MD direction) and the width direction (TD direction). The tensile strength is more preferably 200 MPa or more, and even more preferably 220 MPa or more. The upper limit of the tensile strength is not particularly limited, but is preferably, for example, 500 MPa or less, more preferably 400 MPa or less, and even more preferably 350 MPa or less. If the tensile strength is within the above range, the film has excellent handleability when processed into a laminate for a circuit board suitable for high-speed communication applications, and can suppress defects and cracks that occur at the ends of the film.

[0042] The liquid crystal polyester film of the present invention preferably has low anisotropy in the machine direction (MD) and width direction (TD). In particular, the tensile strength F(TD) in the width direction of the film relative to the tensile strength F(MD) in the machine direction of the film (i.e., F(TD) / F(MD)) is preferably 0.5 to 1.5, more preferably 0.75 to 1.25, even more preferably 0.85 to 1.15, and particularly preferably 0.90 to 1.10. If the tensile strength F(TD) in the width direction of the film relative to the tensile strength F(MD) in the machine direction of the film is within the above range, the anisotropy of the mechanical and electrical properties of the film is small, and it can be suitably used for applications such as laminates for circuit boards suitable for high-speed communication applications.

[0043] The liquid crystal polyester film of the present invention preferably has a dielectric loss tangent of 0.0025 or less, more preferably 0.0024 or less, even more preferably 0.0022 or less, and particularly preferably 0.0020 or less. The liquid crystal polyester film of the present invention preferably has a relative dielectric constant of 2.0 to 4.0. The relative dielectric constant is more preferably 2.5 to 3.9, more preferably 2.6 to 3.8, and even more preferably 2.8 to 3.8. The dielectric properties including the standard dielectric loss tangent and the relative dielectric constant can be measured by a cavity resonator perturbation method.

[0044] The liquid crystal polyester film of the present invention can be further subjected to a heat treatment to relax the orientation of the molecular chains and improve the film dimensional stability. The heat treatment can be a conventionally known method, for example, a contact heat treatment, a non-contact heat treatment, etc., and the type is not particularly limited.

[0045] [Metal laminate film] The liquid crystal polyester film of the present invention may be used as a metal laminate film by laminating a metal layer thereon. When laminating the metal layer, the surface of the liquid crystal polyester film on which the metal layer is to be laminated may be subjected to corona discharge treatment, ultraviolet irradiation treatment or plasma treatment in order to increase adhesive strength.

[0046] Examples of the method for laminating a metal layer on the liquid crystal polyester film of the present invention include (1) a method for attaching a liquid crystal polyester film to a metal foil by heat and pressure bonding, (2) a method for attaching a liquid crystal polyester film and a metal foil with an adhesive, and (3) a method for forming a metal layer on a liquid crystal polyester film by vapor deposition. Among them, the lamination method (1) is a method for pressing the liquid crystal polyester film to a metal foil at a temperature near the flow start temperature of the liquid crystal polyester film using a press or a heated roll, and is recommended because it can be easily performed. Examples of the adhesive used in the lamination method (2) include hot melt adhesives and polyurethane adhesives. Among them, epoxy group-containing ethylene copolymers are preferably used as adhesives. Examples of the lamination method (3) include ion beam sputtering, high frequency sputtering, direct current magnetron sputtering, and glow discharge. Among them, high frequency sputtering is preferably used.

[0047] Examples of metals used in the metal layer include gold, silver, copper, copper alloys, nickel, nickel alloys, aluminum, aluminum alloys, iron, and iron alloys. Copper is preferred for tab tapes and circuit boards, and aluminum is preferred for capacitors. Examples of the structure of the metal laminate film thus obtained include a two-layer structure of a liquid crystal polyester film and a metal layer, a three-layer structure in which metal layers are laminated on both sides of a liquid crystal polyester film, and a five-layer structure in which liquid crystal polyester films and metal layers are alternately laminated. The laminate may be heat-treated as necessary for the purpose of developing high strength. The thickness of the metal layer is not particularly limited, but is preferably 1.5 to 1000 μm, more preferably 2 to 500 μm, even more preferably 5 to 150 μm, and particularly preferably 7 to 100 μm. If the thickness is thinner than this range, the mechanical strength is poor, and if the thickness is thicker than the above range, the handling and processability are poor.

[0048] The circuit board of the present invention includes at least one conductor layer and at least one insulator (or dielectric) layer, and the form is not particularly limited as long as the liquid crystal polyester film of the present invention is used as the insulator (or dielectric), and it can be used as various high-frequency circuit boards by known or conventional means. The circuit board may also be a circuit board (or a semiconductor element mounting board) on which a semiconductor element (e.g., an IC chip) is mounted.

[0049] The conductor layer used in the circuit board of the present invention is formed, for example, from at least a metal having electrical conductivity, and a circuit pattern is formed on this conductor layer by using a known circuit processing method. The conductor forming the conductor layer may be various metals having electrical conductivity, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof. In addition, a circuit pattern may be formed on the metal layer portion of the above-mentioned metal laminate film. EXAMPLES

[0050] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0051] The following resins were used in the examples and comparative examples. (Thermoplastic Liquid Crystal Polyester) LCP (1): A thermoplastic liquid crystal polyester consisting of a constitutional unit derived from p-hydroxybenzoic acid and a constitutional unit derived from 6-hydroxy-2-naphthoic acid (LAPEROS A950RX manufactured by Polyplastics Co., Ltd., melting point: 280°C, softening point: 266°C). LCP (2): Thermoplastic liquid crystal polyester consisting of a constitutional unit derived from p-hydroxybenzoic acid, a constitutional unit derived from 6-hydroxy-2-naphthoic acid, and a constitutional unit derived from terephthalic acid (LAPEROS C950RX manufactured by Polyplastics Co., Ltd., melting point: 320°C, softening point: 303°C). (amorphous polymer) Amorphous polymer (1): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX2001, manufactured by Eastman Chemical Company, Tg: 116°C) Amorphous polymer (2): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX1001, manufactured by Eastman Chemical Company, Tg: 108°C) Amorphous polymer (3): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from ethylene glycol (PETG GN001, manufactured by Eastman Chemical Company, Tg: 90°C) Amorphous polymer (4): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from ethylene glycol (PCTG DN011, manufactured by Eastman Chemical Co., Tg: 90°C) Amorphous polymer (5): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from isophthalic acid (PCTA AN004, manufactured by Eastman Chemical Company, Tg: 90°C) Amorphous polymer (6): Polyarylate resin (U-polymer U-100, manufactured by Unitika Ltd., Tg: 193°C) Amorphous polymer (7): Polysulfone resin (BASF Ultrason S3010, Tg: 187°C) Amorphous polymer (8): Polysulfone resin (Solvay Udel P-1700 NT11, Tg: 185°C) Amorphous polymer (9): Polymer alloy of polyetherimide resin and polyethylene terephthalate resin (ULTEM DU319 manufactured by SABIC, Tg: 185℃) Amorphous polymer (10): Polycarbonate resin (SABIC LEXAN XHT3143T, Tg: 175°C) Amorphous polymer (11): Polymer alloy of polyphenylene ether resin and polystyrene resin (NORYL EFN4230S, manufactured by SABIC, Tg: 175℃) Amorphous polymer (12): Polymethyl methacrylate resin (Acrypet VH001, manufactured by Mitsubishi Chemical Corporation, Tg: 100°C) (Additives) Polyester elastomer: Block copolymer of polybutylene terephthalate and polytetramethylene glycol (PBT / PTMG) The softening point was measured according to JIS K 7196 (1991) by preparing samples with a length of 5 mm, width of 5 mm, and thickness of 0.05 mm, and using a thermomechanical analyzer (manufactured by SII NanoTechnology, model number: TMA / SS 7100) as the measuring device, under conditions of a nitrogen atmosphere, a heating rate of 5°C / min, and a temperature range of 30°C to 350°C, by inserting a transparent quartz pin (tip diameter φ0.5 mm) under a load of 50 gf into the stacked samples. The glass transition temperature was measured using the value in the manufacturer's catalog.

[0052] (1) Manufacturing of molded products by injection molding The thermoplastic liquid crystal polyester resin composition was premixed in the ratio shown in Table 1, and then extruded at a cylinder temperature of 300°C using an injection molding machine (Handtruder M-1, Toyo Seiki Seisakusho Co., Ltd.) to obtain a rectangular test piece (length 82 mm, width 10 mm, thickness 4 mm). The obtained rectangular test piece was visually evaluated for the presence or absence of foaming and for its appearance. The evaluation results are shown in Table 1.

[0053] [Table 1]

[0054] As a result of the basic evaluation of the injection molded product, the resin composition of Reference Example 7, which contains a polycarbonate resin as the amorphous polymer, foamed during injection molding, and the injection molded product yellowed, resulting in a poor appearance. The resin composition of Reference Example 8, which contains a polymer alloy of polyphenylene ether resin and polystyrene resin as the amorphous polymer, and the resin composition of Reference Example 9, which contains a polymethyl methacrylate resin as the amorphous polymer, foamed during injection molding. The resin compositions of Reference Examples 1 to 6 showed no problems in processability and appearance in the evaluation of injection molding.

[0055] (2) Manufacture of film by blown film extrusion After premixing the thermoplastic liquid crystal polyester resin composition in the ratio shown in Table 2, it was heated and kneaded in a single screw extruder, melt extruded in a bubble shape from a circular inflation die (diameter 25 mm) at a discharge rate of 3 kg / h, and the bubble was stretched under the conditions of draft ratio = 2 and blow ratio = 5, and a liquid crystal polyester film with a thickness of 50 μm was obtained by inflation extrusion molding. The resin temperature of the bubble during film formation was controlled so that it was at the softening point of -40 ° C or higher from the contact position with the stabilizer to the pinch roll. The film formability and physical properties of the film obtained by the following evaluation method are shown in Table 2.

[0056] (Film-forming ability: bubble stability) When a film was produced by inflation extrusion molding, the lateral vibration of the bubble end in the TD direction at the position where the molten bubble had completed expansion was visually observed and evaluated according to the following criteria. ○: Almost no bubble fluctuation ○△: The bubble repeatedly sways slightly in the TD direction and is not stable. △: The bubble repeatedly swings in the TD direction and is unstable. (Film-forming: Bubble holes) When a film was produced by inflation extrusion molding, the appearance of bubbles of molten resin extruded from a die was visually observed and evaluated according to the following criteria. ○: No holes in the bubble ○△: Small holes rarely occur in the bubble. △: Multiple small holes in the bubble (air leaking from inside the bubble affects the bubble shape) ×: Many holes were formed in the bubbles, making continuous film production impossible. (Film forming: Film wrinkles) The obtained film was visually inspected for slackness and wrinkles in the TD direction (horizontal wrinkles) and evaluated according to the following criteria. ○: No slack or wrinkles are observed in the film. ○△: Slight wrinkles are visible on the film △: There are several faint wrinkles and looseness in the film. △×: Several faint and clear wrinkles are observed on the film, and slack is observed. ×: Several clear wrinkles are observed on the film, and slack is observed.

[0057] (Physical properties: tensile strength) In accordance with ASTM D882, samples cut to a size of 190 mm x 15 mm were measured using an autograph AGS-500NX (Shimadzu Corporation) at a tensile speed of 12.5 mm / min and a chuck distance of 125 mm. The measurement temperature was 23°C. Measurements were performed in both the machine direction (MD) and the width direction (TD) of the film. (Physical properties: relative dielectric constant, dielectric tangent) Using a cavity resonator (10 GHz resonator manufactured by AET) and a network analyzer (MS46122B manufactured by Anritsu), the relative dielectric constant and dielectric loss tangent were measured in the 10 GHz frequency band under an environment of 23°C temperature and 65% RH. The measurements were performed in both the machine direction (MD) and the width direction (TD) of the film.

[0058] [Table 2]

[0059] As shown in Table 2, the liquid crystal polyester films of Examples 1 to 12 containing an amorphous copolyester having a glass transition temperature of 80 to 200 ° C. suppressed the formation of bubbles and lateral vibrations extruded from a die, and showed results that a stable film can be formed, and a smooth film without slack or wrinkles can be obtained. In addition, the liquid crystal polyester films of Examples 1 to 12 showed results that improved film forming processability while maintaining the excellent mechanical properties and electrical properties of thermoplastic liquid crystal polyester.

[0060] On the other hand, the liquid crystal polyester film of Comparative Example 1 containing polyarylate as an amorphous polymer showed a certain effect on bubble stability and bubble hole formation, but the film showed slackness and horizontal wrinkles, and a smooth film was not obtained. This result shows that blending an amorphous copolyester with a glass transition temperature of 80 to 200°C is important for improving the sliding properties of the bubble near the softening point.

[0061] The resin compositions of Comparative Examples 2 to 4, which contain a polymer alloy of polysulfone resin, polyetherimide resin and polyethylene terephthalate resin as an amorphous polymer, show a certain effect on bubble stability and bubble hole formation, but the film shows frequent slackness and horizontal wrinkles, and only films with difficult physical property evaluation were obtained. In addition, in Reference Example 10, which was produced by film production using only thermoplastic liquid crystal polyester, frequent holes were produced in the bubbles, and film production could not be performed continuously, so a film could not be obtained. [Industrial Applicability]

[0062] As described above, the liquid crystal polyester film obtained by the present invention is used for electrical insulation of motors and transformers, element formation film of flexible solar cells, etc. by taking advantage of its excellent mechanical properties, electrical properties, dimensional stability, heat resistance, etc. It can also be used in the acoustic field, such as surface protection films and diaphragms. The metal laminate film of the present invention can also be used for circuit boards, capacitors, electromagnetic wave shielding materials, etc. The circuit board of the present invention may be used for various transmission lines and antennas (for example, microwave or millimeter wave antennas), and may also be used for antenna devices in which an antenna and a transmission line are integrated.

Claims

1. A liquid crystal polyester-based resin composition comprising a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B), wherein the amorphous copolyester (B) has a glass transition temperature of 80°C or higher and 200°C or lower, and the blending ratio of the thermoplastic liquid crystal polyester (A) to the amorphous copolyester is (A):(B)=50-99.5% by weight:0.5-50% by weight.

2. The liquid crystal polyester resin composition according to claim 1, characterized in that the thermoplastic liquid crystal polyester (A) contains at least one selected from the group consisting of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid.

3. 2. The liquid crystal polyester resin composition according to claim 1, wherein the amorphous copolyester (B) contains a structural unit derived from a terephthalic acid monomer and a structural unit derived from 1,4-cyclohexanedimethanol.

4. The liquid crystal polyester resin composition according to claim 1, characterized in that the amorphous copolyester (B) contains a structural unit derived from a terephthalic acid monomer, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol.

5. 2. The liquid crystal polyester resin composition according to claim 1, wherein the thermoplastic liquid crystal polyester (A) has a melting point of 250° C. or higher.

6. 2. The liquid crystal polyester resin composition according to claim 1, which is for inflation extrusion molding.

7. A liquid crystal polyester film comprising the resin composition according to any one of claims 1 to 6.

8. 8. A metal laminate film, comprising the liquid crystal polyester film according to claim 7, and a metal layer laminated on one or both sides of the liquid crystal polyester film.

9. A circuit board comprising at least one conductor layer and the liquid crystal polyester film according to claim 7.

Citation Information

Patent Citations

  • Polymer alloy and its film

    JP2000290512A

  • Liquid crystal polymer composition

    JP2020193261A